A Review On Current Diagnostic Tools And Potential Optical Absorption Spectroscopy For Hfmd Detection - Fatin Hamimi Mustafa; Irneza Ismai; Ahmad Aiman Zuhaily Ahmad Munawar; Basmah Abdul Basir; Rafidah Hanim Shueb; Ahmad Adebayo Irekeola; Wan Zakiah Wan Ismail; Juliza Jamaludin; Sharma Rao Balakrishnan; Mus’ab Sahrim; Nik Yusnoraini Yusof (Elsevier, 2024)
Indexed by Scopus/ERA